Globalization of Commercial Banks in Nigeria: Impact of Information and Communication Technology (1988 – 2019) - Ifeanyi, Titus Freeman; Ukah, Ruth C. (Archives of Business Research, 2021)
The study examined the globalization of commercial banks in Nigeria: impact of information and communications technology for the period 1988 to 2019. It was necessitated by the call for more insight on how information and communications technology impacts globalization of commercial banks in Nigeria. It specifically determined the impact of teledensity on loans from non-resident banks to Nigeria, the impact of internet penetration on foreign banks asset in Nigeria, and the impact of banking market size on consolidated foreign claims of Bank of International Settlement in Nigeria. The study adopted ex-post research design in the analysis of data. Data analysis technique is adopted ordinary least squares (OLS) method because of the desirable properties (linearity, unbiasedness and minimum variance, among other unbiased estimators) it possesses. The findings show that ICT plays significant positive role in commercial bank globalization. Recommendations were made on what should be done to ensure the development of the ICT sector in Nigeria.